2013
DOI: 10.1371/journal.pone.0064449
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Lectins from Red and Blue-Green Algae Show Potent In Vitro and In Vivo Activity against Hepatitis C Virus

Abstract: Hepatitis C virus (HCV) infection is a significant public health problem with over 170,000,000 chronic carriers and infection rates increasing worldwide. Chronic HCV infection is one of the leading causes of hepatocellular carcinoma which was estimated to result in ∼10,000 deaths in the United States in the year 2011. Current treatment options for HCV infection are limited to PEG-ylated interferon alpha (IFN-α), the nucleoside ribavirin and the recently approved HCV protease inhibitors telaprevir and boceprevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 42 publications
2
121
0
4
Order By: Relevance
“…The secreted small luciferase (nanoluciferase; Nlucsec) fragment from the pNL1.3 vector (Promega) was inserted into the self-cleaving 2A peptides of Thosea asigna virus, which generates two separated proteins (25) between p7 and NS2 of pJFH1-E2p7NS2mt, and the resulting plasmid was designated pJFH1-E2p7NS2mt-Nlucsec. pCon1/JFH1 (genotype 1b) was used for the production of chimeric virus (26). The plasmids used in this study were confirmed by sequencing with an ABI 3130 genetic analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…The secreted small luciferase (nanoluciferase; Nlucsec) fragment from the pNL1.3 vector (Promega) was inserted into the self-cleaving 2A peptides of Thosea asigna virus, which generates two separated proteins (25) between p7 and NS2 of pJFH1-E2p7NS2mt, and the resulting plasmid was designated pJFH1-E2p7NS2mt-Nlucsec. pCon1/JFH1 (genotype 1b) was used for the production of chimeric virus (26). The plasmids used in this study were confirmed by sequencing with an ABI 3130 genetic analyzer (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…Kemampuan lektin untuk mengikat karbohidrat secara spesifik pada permukaan sel (glikokonjugat), memungkinkan protein ini dapat dikembangkan untuk berbagai tujuan, termasuk untuk deteksi dan identifikasi kelompok darah dan mikroorganisme, determinasi karbohidrat dalam suatu larutan, juga untuk pemurnian glikoprotein (Van Damme, 2014). Karena kemampuannya untuk mengikat karbohidrat di permukaan sel secara spesifik tersebut, lektin juga mempunyai banyak peran penting dalam interaksi antara host-patogen, komunikasi sel-sel, mengenali dan mengikat karbohidrat yang kemudian menghasilkan efek fungsional untuk menginduksi apoptosis, berperan sebagai antibiotik, antiinflammatory, anti-HIV serta anti agregasi platelet (Liao et al, 2003;Dinh et al, 2011;Sato et al, 2011;Hamid et al, 2013;Takebe et al, 2013). Secara alami, lektin banyak ditemukan pada hampir semua makhluk hidup: tumbuhan, jamur, bakteri, virus, hewan (vertebrata dan avertebrata).…”
Section: Pendahuluanunclassified
“…Antiviral activity against HCV [30,170], HIV-1 [32,169,171], HIV-2 [171], and SARS-CoV [172] has been documented. Unpublished studies have also demonstrated activity versus influenza A virus, and several other enveloped viral pathogens (O'Keefe BR, unpublished).…”
Section: Griffithsin Structure and Mechanism Of Actionmentioning
confidence: 99%
“…In vivo challenges in mice have also been positive, with activity versus: SARS-CoV (intranasal treatments) [172]; Japanese encephalitis virus (JEV) (intraperitoneal treatment) [173]; and HCV (subcutaneous treatmentmouse-human chimeric liver models) [30,170].…”
Section: Griffithsin Structure and Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation